THE GRAVE VIOLATION AGAINST SYRIAN CHILDREN AS A VICTIM KILLING AND MAIMING IN ARMED CONFLICT - Farah Elsa Nova; Sophia Listriani (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2018)
For six years, the conflict in Syria has since evolved into a larger and more complex war. The annual report of the Secretary-General on children and armed conflict show that children are one of the main victim of killing and maiming in Syria.Millions of children are killed by armed conflict and many of them caused by the use of indiscriminate attack, explosive weapon and chemical weapon that all which are prohibited under international humanitarian law as mentioned in common article 3 of Geneva Conventions which is universally applicable at all times both International Armed Conflict and Non International Armed Conflict. The focus of the research is to describe theprotection of children covered by International Humanitarian Law and to describethe measures of Syrian Government and United Nations to protect the children in armed conflict. This research is conducted under normative method. The data is accumulated predominantly on secondary data beside primary and tertiary data by library research through identifying and locating sources that provide actual information or opinion of legal experts. All parties to the armed conflict are bound by the relevant provisions of international humanitarian law. Those matters obligethe parties of the Conflict in Syria to give full protection to the children from the effects of armed conflict. Despite Syria has not signed the 1977 Additional Protocol II yet, Common article 3 of Geneva Convention and Additional Protocol II become applicable automatically when the requirements for an armed conflict are reached. The Protection Children in armed conflict under international humanitarian law is granted as civilians or combatants.The protection of children as civilian and combatans  are enacted in Common Article 3 of Geneva Convention 1949, Additional protocol I and Additional protocolII 1997 to the Geneva Conventions. Syrian Government provides the preventive measures in the Law No. 11 of 2013 about the prohibition of recruitment and use of the children under the age of 18 by armed forces and armed groups. The thesis found that one of the biggest problems is the ICC can not apply its jurisdictionbecauseSyria has not ratified the Rome Statute yet. Furthermore, United Nations established The Resposibility to Protect (R2P) norm as a part of use of force or humanitarian intervention mechanism to achieve a peaceful resolution to the conflict in Syria. The Government efforts are the key solution on the enforcement issue and United Nations shall review the usefulness of the veto to end the violence so that the situation in Syria can be tried either by national courts or ICC where the allegation can be prosecuted.